Silk nanofibers-ZIF hybrid membrane with improved treatment efficiency and highly enhanced water permeability for excellent removal of multiple pollutants from water. Issue 11 (25th October 2021) - Sun, Dina; Meng, Gengping; Sun, Shihao; Guo, Wenting; Hai, Jun; Su, Junxia; Song, Yanxia; Chen, Fengjuan; Wang, Baodui
Abstract : We developed a new and sustainable SNFs-ZIF hybrid membrane with improved treatment efficiency and enhanced water permeability for excellent removal of multiple pollutants including heavy metals, dyes and NO3 − . Abstract : The preparation of membranes with improved treatment efficiency and highly enhanced water permeability remains a distant prospect. Herein, a low-cost hybrid membrane composed of silk nanofibers (SNFs) and zeolitic imidazolate framework (ZIF) was successfully prepared for efficient wastewater treatment. The resulting SNFs-ZIF hybrid membrane breaks the treatment efficiency–water permeability trade-off with both parameters remarkably increasing for wastewater treatment. At a water permeability of 354.06 L m −2 h −1 bar −1, the treatment efficiency of the hybrid membrane for metal ions is close to 100%, and the above operation can be repeated at least 8 times. The water permeability is almost increased by 1–2 orders of magnitude compared with other similar materials. Such remarkably enhanced treatment efficiency and water permeability were attributed to the ability of the SNFs and ZIF to selectively adsorb heavy metal contaminants and the formed hydrophilic interlaced nanochannels in the self-assembly process. Strikingly, the membrane can also be used to recycle palladium (Pd) pollutants by reducing the trapped Pd ions in the membrane at high temperature, leading to the creation of Pd nanoparticles for electrocatalytic reduction of nitrate ions with a NO3 − –N conversion of 87.56% and N2 selectivity of 77% in 60 h. This study provides a feasible strategy for fabricating a high-performance ZIF-functionalized bio-membrane with improved treatment efficiency and highly enhanced water permeability for excellent removal of multiple pollutants from water.